Problem-Based Learning and Canva AI Interactive Multimedia: Enhancing IPAS Learning Outcomes and Motivation in Elementary Education - Dina Erawati; Joko Sulianto; Achmad Buchori (Universitas Pendidikan Ganesha, 2026)
low learning outcomes of Natural and Social Sciences (IPAS) in elementary school students, characterized by suboptimal average scores and completion rates, indicate problems in the learning process. This condition is influenced by the dominance of the lecture method and the limited use of interactive media that can increase student engagement. This study aims to analyze the effect of the Problem-Based Learning (PBL) model supported by Canva AI Interactive Multimedia on student learning outcomes and motivation. The study used a quantitative approach with a quasi-experimental design of the non-equivalent control group design. The subjects were third-grade elementary school students. Data collection was carried out through objective tests to measure learning outcomes and questionnaires to measure learning motivation. Data analysis was carried out using inferential statistics, such as the mean difference test (t-test) to compare results between the experimental and control groups. The results showed that the application of the PBL model assisted by Canva AI Interactive Multimedia significantly improved student learning outcomes and motivation, as indicated by a higher average posttest score for the experimental group compared to the control group. In conclusion, the integration of the PBL model with AI-based interactive multimedia support is effective in improving the quality of science and science learning in elementary schools. The implications of this research suggest that utilizing AI-based visual technology in problem-based learning can be an innovative strategy for enhancing student engagement and learning outcomes.